Method for producing powdered activated carbon molded product
By heating and pressurizing plant-derived powdered activated carbon, the formation of silicon carbide enhances the adsorption and heat resistance of the molded bodies, addressing the performance reduction caused by silicon dioxide.
Patent Information
- Application Number
- JP2023175102
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-10
AI Technical Summary
Plant-derived powdered activated carbon, used to form molded bodies, contains silicon dioxide that reduces its adsorption performance and heat resistance due to blocked pores and lower melting points.
Heating plant-derived powdered activated carbon to 650° C to 800° C or 1400° C to 1600° C in a non-oxidizing atmosphere and mechanically pressurizing it to form a molded body, which increases the specific surface area and converts silicon dioxide into silicon carbide, enhancing adsorption and heat resistance.
The process prevents deterioration in adsorption performance and heat resistance of plant-derived powdered activated carbon molded bodies, improving their robustness and acid resistance.
Smart Images

Figure 2025065714000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a powdered activated carbon molded body obtained by molding powdered activated carbon, and a method for producing the same. [Background technology]
[0002] Conventionally, activated carbon, which has pores of various sizes and has been treated to enhance the efficiency of adsorption of substances, has been widely used as an adsorbent for the treatment of liquids or gases for the purposes of deodorization, decolorization, filtration, etc. Since activated carbon is in powder form, it is possible to improve convenience and ease of handling by forming this powdered activated carbon into a molded body. However, since powdered activated carbon does not have adhesive properties or sintering properties, it is difficult to form powdered activated carbon into a molded body by normal pressure or heating.
[0003] Therefore, a binder containing an organic component is added to the powdered activated carbon and kneaded to produce a powdered activated carbon molded body. However, since the binder binds the powders together, the pores of the powdered activated carbon are covered with the binder, hindering the adsorption function of the powdered activated carbon molded body. In addition, the ratio of powdered activated carbon per unit volume is reduced by the binder, so the adsorption performance per unit volume of the powdered activated carbon molded body is reduced.
[0004] In addition, there are cases where the organic components contained in the binder generate gases that can cause problems. For example, in a nuclear fusion reactor that maintains a high vacuum state using a cryopump, if a powdered activated carbon molded body using a binder is used as an adsorbent for the cryopump, the degree of vacuum in the nuclear fusion reactor will actually decrease due to the gases originating from the binder.
[0005] Therefore, Patent Document 1 discloses a method of forming a compact by sintering a powdered adsorbent by plasma discharge while applying pressure to the powdered adsorbent without using a binder. The spark plasma sintering method is a processing method of sintering a workpiece by mechanical pressure and electrical heating. However, Patent Document 1 does not disclose conditions such as temperature and pressure in the spark plasma sintering method.
[0006] On the other hand, powdered activated carbon molded bodies are sometimes used as adsorbents for cryopumps, and in this case, it is generally required that the pore distribution of the powdered activated carbon molded bodies has a peak in the diameter range of 2 nm to 10 nm among mesopores (diameter: 2 nm to 50 nm).
[0007] Here, Patent Document 2 discloses a powdered activated carbon molded body having a pore distribution peak at around 4 nm. This powdered activated carbon molded body is sintered by applying pressure of 20 MPa to a porous carbon powder and heating it to 1000°C by electrical heating using a spark plasma sintering method. A comparison of the specific surface area, total pore volume, pore distribution, etc. between this sintered product and the original powdered activated carbon before sintering is shown. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 11-239723 [Patent Document 2] JP 2020-50531 A Summary of the Invention [Problem to be solved by the invention]
[0009] The porous carbon powder of Patent Document 2 is a high-performance powdered activated carbon with few impurities that is industrially produced through a complicated process, and is expensive although it has excellent adsorption properties, heat resistance, etc. Instead of this high-performance powdered activated carbon, by molding a powdered activated carbon derived from plants that is easily and inexpensively available, it is possible to produce a powdered activated carbon molded body at a lower cost than that of Patent Document 2.
[0010] Generally, powdered activated carbon derived from plants is made from raw materials such as coconut shells, sawdust, rice husks, and rice straw. In particular, powdered activated carbon made from rice-derived raw materials such as rice husks and rice straw is easily available in Japan. In this powdered activated carbon derived from plants, silicon absorbed from the soil remains in the form of silicon dioxide (SiO 2 Such powdered activated carbon containing silicon dioxide can be formed into a molded article by the spark plasma sintering method, as described in Patent Documents 1 and 2.
[0011] However, the silicon contained in the powdered activated carbon compact reduces its performance as an adsorbent. For example, silicon dioxide blocks the pores, reducing the adsorption ability of the adsorbent. In addition, silicon dioxide, which has a lower melting point than carbon, melts in a high-temperature environment, reducing the heat resistance of the adsorbent.
[0012] The present invention has been made to solve the above-mentioned problems, and has an object to provide a powdered activated carbon molding that can prevent a decrease in performance as an adsorbent caused by plant-derived powdered activated carbon, and a method for producing the powdered activated carbon molding. [Means for solving the problem]
[0013] The powdered activated carbon molding of the invention of claim 1 is a powdered activated carbon molding obtained by heating plant-derived powdered activated carbon to 650°C to 800°C in a non-oxidizing atmosphere by an electric current heating method and simultaneously molding the same by mechanical pressure, and is characterized in that it contains silicon dioxide and has a larger specific surface area than the powdered activated carbon.
[0014] According to the above-mentioned configuration, the powdered activated carbon molded body contains silicon dioxide because it is a powdered activated carbon derived from plants, but by forming it into a powdered activated carbon molded body, the specific surface area is made larger than that of the original powdered activated carbon. Therefore, when the powdered activated carbon molded body is used as an adsorbent, even if it contains silicon dioxide, it is possible to prevent a decrease in the adsorption performance of the adsorbent, which depends on the specific surface area.
[0015] The powdered activated carbon molding of the invention of claim 2 is a powdered activated carbon molding obtained by heating plant-derived powdered activated carbon to 1400°C to 1600°C in a non-oxidizing atmosphere by an electric current heating method and simultaneously molding the same by mechanical pressure, and is characterized by containing silicon carbide.
[0016] According to the above-mentioned configuration, even if the plant-derived powdered activated carbon contains silicon dioxide, silicon carbide is formed by forming the powdered activated carbon into a molded body of silicon carbide. When this powdered activated carbon molded body is used as an adsorbent, silicon carbide has a high melting point, and its heat resistance is improved compared to when the powdered activated carbon molded body contains, for example, silicon dioxide, and it is possible to prevent a decrease in performance as an adsorbent. In addition, silicon carbide is chemically stable and does not dissolve in, for example, nitric acid, which dissolves carbon, so that its acid resistance is improved and its performance as an adsorbent is improved.
[0017] The powdered activated carbon molded body of the invention of claim 3 is the powdered activated carbon molded body of the invention of claim 1 or 2, which has a bulk density of 0.5 g / cm 3 The present invention is characterized in that: According to the above-mentioned configuration, it is possible to obtain a bulk density sufficient to make the adsorbent robust.
[0018] The method for producing powdered activated carbon molded bodies according to the invention of claim 4 is characterized in that the plant-derived powdered activated carbon is heated to 650° C. to 800° C. in a non-oxidizing atmosphere by an electric heating method and mechanically pressurized at 30 MPa. According to the above-mentioned configuration, even if the plant-derived powdered activated carbon contains silicon dioxide, by forming it into a powdered activated carbon molded body, the specific surface area can be made larger than that of the original powdered activated carbon. Therefore, when the powdered activated carbon molded body is used as an adsorbent, even if it contains silicon dioxide, it is possible to prevent a decrease in the adsorption performance of the adsorbent, which depends on the specific surface area.
[0019] The method for producing powdered activated carbon molded bodies according to the invention of claim 5 is characterized in that the plant-derived powdered activated carbon is heated to 1400° C. to 1600° C. in a non-oxidizing atmosphere by an electric heating method and mechanically pressurized at 30 MPa. According to the above-mentioned configuration, even if the plant-derived powdered activated carbon contains silicon dioxide, silicon carbide is produced by forming the powdered activated carbon into a powdered activated carbon molded body. When this powdered activated carbon molded body is used as an adsorbent, silicon carbide has a high melting point, and the heat resistance is improved compared to when the powdered activated carbon molded body contains, for example, silicon dioxide, and the performance as an adsorbent can be prevented from decreasing. In addition, silicon carbide is chemically stable and does not dissolve in, for example, nitric acid, which dissolves carbon, so that the performance as an adsorbent is improved. Effect of the Invention
[0020] According to the powdered activated carbon molded body and the method for producing the powdered activated carbon molded body of the present invention, it is possible to prevent a decrease in the performance of the powdered activated carbon as an adsorbent, which is caused by the plant-derived powdered activated carbon. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a diagram showing the configuration of a pulse current sintering machine used in a spark plasma sintering method. [Diagram 2] 2 is a graph (adsorption isotherm) showing the adsorption amount of the powdered activated carbon molded body formed by the apparatus of FIG. 1. [Diagram 3] FIG. 2 is a pore size distribution diagram of a powdered activated carbon molded body formed by the apparatus of FIG. 1. [Figure 4] 2 shows the results of a surface analysis of a powdered activated carbon molding formed by the apparatus of FIG. 1. [Diagram 5] 2 is an X-ray diffraction pattern of a powdered activated carbon molding formed by the apparatus of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, the embodiment for carrying out the present invention will be described in detail, however, the present invention is not limited to the following embodiment.
[0023] The powdered activated carbon compact is formed by heating only powdered activated carbon derived from plants such as coconut shells, sawdust, rice husks, rice straw, etc., by electric current heating, without using a binder that is a gas generating source. The electric current heating method is a method in which an electric current is passed through a conductive object to be treated, and the object is directly heated by Joule heat.
[0024] A suitable electric current heating method is the spark plasma sintering method (SPS method). In the SPS method, a direct current pulse current is passed through the workpiece to heat it and mechanically pressurize (compress) it. It is believed that the powdered activated carbon of the workpiece is locally heated, for example, at the contact points between the particles of the powdered activated carbon, at the fine structure in the particles of the powdered activated carbon, and at the functional groups and impurity elements contained in the particles of the powdered activated carbon, and that this promotes bonding between the particles of the powdered activated carbon.
[0025] Commercially available powdered activated carbon is made by carbonizing and activating raw materials such as coconut shells, sawdust, rice husks, rice straw, and other plants, coal, petroleum, and synthetic resins. Rice-derived raw materials such as rice husks and rice straw are preferred because they are easily available in Japan. Plants contain silicon absorbed from the soil and accumulated therein, mainly as silicon dioxide. Therefore, plant-derived powdered activated carbon contains a few percent by mass of silicon that was not completely removed by treatment with, for example, chemicals after carbonization.
[0026] In forming powdered activated carbon compacts by the SPS method, a predetermined amount of powdered activated carbon is filled between a pair of punches made of artificial graphite that are inserted facing each other into a cylindrical die made of artificial graphite, and the powdered activated carbon is mechanically compressed by the pair of punches. The atmosphere to which the powdered activated carbon is exposed at this time is a non-oxidizing atmosphere to prevent the powdered activated carbon, the die, the punches, etc. from being worn down due to oxidation of carbon, and is a vacuum atmosphere or an inert gas atmosphere such as a nitrogen atmosphere.
[0027] The maximum temperature (heating temperature) during heating of powdered activated carbon is about 600°C to 2000°C, which is sufficiently lower than the sublimation temperature of carbon (3642°C at normal pressure) and the triple point (4327°C at 10.8 MPa), but is still high. If the temperature is less than 600°C, the bonding between the particles of powdered activated carbon is not promoted, making it difficult to form a powdered activated carbon molded body. On the other hand, if the temperature exceeds 2000°C, the pores of the powdered activated carbon are likely to deform, and the pore volume and specific surface area are thought to decrease. In terms of maintaining or increasing the mesopores and specific surface area, the heating temperature is preferably 600°C or higher and less than 1000°C, and more preferably 650°C to 800°C.
[0028] Furthermore, in order for the powdered activated carbon molded body to contain silicon carbide, the heating temperature is preferably 1400° C. to 2000° C. If the heating temperature is less than 1400° C., the reaction that converts silicon dioxide and the like contained in the powdered activated carbon into silicon carbide does not occur sufficiently.
[0029] The rate of temperature rise during heating can be appropriately set, for example, from 2° C. / min to 100° C. / min. The rate of temperature rise is preferably from 5° C. / min to 50° C. / min, and more preferably from 5° C. / min to 20° C. / min.
[0030] The time for which the powdered activated carbon molded body is heated may be, for example, 5 to 60 minutes. If the time is less than 5 minutes, uneven heating may occur in the molded body. If the time is more than 60 minutes, the production efficiency of the powdered activated carbon molded body will decrease.
[0031] The pressure mechanically applied to the powdered activated carbon can be appropriately set so that the powdered activated carbon is sufficiently solidified into a molded body, and is, for example, preferably 5 MPa to 50 MPa, and more preferably 10 MPa to 30 MPa.
[0032] The bulk density of the powdered activated carbon compact is 0.5 g / cm 3 If the bulk density is lower than this range, sufficient strength cannot be ensured, and there is a risk that the material may become difficult to handle.
[0033] The powdered activated carbon used for molding was Triporous (registered trademark) (manufactured by Sony Corporation), which was manufactured using rice husks as the raw material, and powdered activated carbon molded bodies were formed by the SPS method. The equipment used in the SPS method was a pulse current sintering machine LABOX-325R (manufactured by Sinterland Co., Ltd.) (maximum pressure 30 kN, maximum pulse current output 2500 A).
[0034] As shown in FIG. 1, the powdered activated carbon 2 derived from rice, which is the material to be treated, is placed in a pulse current sintering machine 1. Specifically, 0.9 g to 1 g of the powdered activated carbon 2 is loaded between a pair of punches 4 and 5 (diameter 15 mm, length 20 mm) made of artificial graphite, which are inserted from above and below into a cylindrical die 3 (outer diameter 35 mm, inner diameter 15 mm, height 30 mm) made of artificial graphite. The powdered activated carbon 2 is mechanically pressed (compressed) by the pair of punches 4 and 5. The diameter of the punches 4 and 5 is adjusted so that they can slide within the die 3. In order to prevent the powdered activated carbon 2 from adhering to the punches 4 and 5, graphite sheets (not shown) having the same diameter as the punches 4 and 5 and a thickness of 0.2 mm are sandwiched between the powdered activated carbon 2 and the punches 4 and 5, respectively.
[0035] As the lower jig, first to third spacers 6 to 8 made of artificial graphite and having different sizes are arranged so that they become smaller toward the punch 5 side. Similarly, as the upper jig, first to third spacers 6 to 8 made of artificial graphite and having different sizes are arranged so that they become smaller toward the punch 4 side.
[0036] A 5 mm thick carbon felt 9 for thermal insulation is attached to the outer periphery of the die 3 so as to cover the die 3. A casing 10 is arranged to airtightly cover the upper and lower jigs, the die 3 with the carbon felt 9 attached, and the pair of punches 4, 5.
[0037] The pulse current sintering machine 1 has a pressurizing unit 11, a pulse power supply 12, a cooling mechanism 13, and a vacuum unit 14. The pressurizing unit 11 pressurizes the powdered activated carbon 2 arranged between the punches 4 and 5 via an upper jig and a lower jig. The pulse power supply 12 applies a DC pulse current to the powdered activated carbon 2 via the punches 4 and 5. The cooling mechanism 13 cools at least one pair of punches 4 and 5 by air cooling or water cooling. The vacuum unit 14 evacuates the inside of the casing 10 to maintain a vacuum state. The temperature of the side portion of the die 3 that is not covered with the carbon felt 9 is measured by a radiation thermometer 15 as the temperature of the powdered activated carbon 2 being heated.
[0038] The molding conditions common to Examples 1 to 4 of the present invention and Comparative Examples 1 to 4 are shown below. The atmosphere was vacuum at about 20 Pa. Pressurization by the pressurizing unit 11 was started during temperature rise when the temperature reached a temperature 100° C. lower than the target heating temperature. The temperature rise rate was 20° C. / min or more and 100° C. / min or less until the start of pressurization, and was 20° C. / min from the start of pressurization until the heating temperature was reached. The heating temperature was maintained for 10 minutes. After the retention time had elapsed, the heating and pressurization were stopped, and the powdered activated carbon 2 was cooled by the cooling mechanism 13 to about 50° C., at which point it could be removed, and the powdered activated carbon molded body obtained by molding the powdered activated carbon 2 was removed from the die 3 . When a graphite sheet was attached to the removed powdered activated carbon molded body, the graphite sheet was carefully removed so as not to damage the powdered activated carbon molded body.
[0039] Table 1 shows the individual molding conditions (heating temperature, applied pressure) for Examples 1 to 4 and Comparative Examples 1 to 4, the measurement results for the obtained powdered activated carbon molded bodies, and, as a reference example, the measurement results for powdered activated carbon that was not subjected to molding.
[0040] [Table 1]
[0041] In Examples 1 to 4, the heating temperatures were 650°C, 800°C, 1400°C, and 1600°C, respectively, and the applied pressure was all 30 MPa. In Comparative Examples 1 to 3, the heating temperatures were all 1000°C, and the applied pressures were 10 MPa, 20 MPa, and 30 MPa, respectively. In Comparative Example 4, the heating temperature was 1200°C, and the applied pressure was 30 MPa. The powdered activated carbon molded bodies of Examples 1 to 4 and Comparative Examples 1 to 4 all had a bulk density of 0.50 g / cm. 3 As described above, the molded powdered activated carbon is robust and does not crumble easily, making it easy to handle. The compressive strength of the molded powdered activated carbon of Example 1, which has the smallest bulk density, is about 1.1 MPa, and it is considered that the molded powdered activated carbon of Examples 2 to 4 and Comparative Examples 1 to 4 have compressive strengths equal to or greater than this.
[0042] The powdered activated carbon molded bodies of Examples 1 to 4 and Comparative Examples 1 to 4 were measured for specific surface area, pore volume, and pore size distribution using a gas adsorption tester (Quantachrome Instruments Autosorb iQ-XR-XR (2 Stat.) Viton). From each powdered activated carbon molded body, approximately 0.03 g to 0.07 g of powdered activated carbon that had been crushed and returned to powder form was taken out as a measurement sample and measured. As a reference example, powdered activated carbon that had not been subjected to molding treatment was also measured.
[0043] As a pretreatment, the measurement sample was heated at 117°C for 3 hours or more, and then degassed under reduced pressure at about 120°C for 2 hours or more. The measurement was carried out according to a conventional method, using liquid nitrogen at 77K and nitrogen gas as the adsorption gas. The amount of adsorption and desorption of nitrogen gas versus relative pressure (pressurization and depressurization) was measured, and the adsorption isotherm shown in Figure 2 was obtained.
[0044] In Figure 2, the amount of adsorbed nitrogen gas is plotted against the relative pressure. In the adsorption / desorption isotherms of all the measured samples, hysteresis occurs between the adsorption and desorption processes. The equilibrium adsorption amount during desorption is greater than the equilibrium adsorption amount during adsorption. According to the classification of the International Union of Pure and Applied Chemistry (IUPAC), these are classified as Type IV adsorption isotherms.
[0045] The specific surface area of each measurement sample was determined by the Brunauer-Emmett-Teller method (BET method). That is, the monolayer adsorption amount was determined from the slope and intercept of the BET plot at relative pressures of 0.05 to 0.3, and the specific surface area was calculated. The pore volume of each measurement sample was calculated based on the nitrogen adsorption amount at relative pressures of 0.99 or more. Table 1 shows the specific surface area and pore volume as pore characteristics of the powdered activated carbon of the Reference Example and the powdered activated carbon shaped bodies of Examples 1 to 4 and Comparative Examples 1 to 4.
[0046] The pore size distribution was determined by the Barrett-Joyner-Halenda method (BJH method) assuming that the shape of the mesopores was cylindrical. Figure 3 shows curves showing the pore size (diameter) distribution (pore volume for pore diameters of 2 nm to 10 nm in desorption) of Reference Example, Examples 1 to 4, and Comparative Examples 1 to 4.
[0047] The height of the mesopore curve having a peak at around 3.8 nm is higher in the powdered activated carbon molded bodies of Examples 1 and 2 than in the untreated powdered activated carbon of the Reference Example. This indicates that the volume of the mesopores after molding by the SPS method is larger than that before the treatment. In addition, the specific surface area is 754.0 m in Example 1. 2 / g, and 721.3 m in Example 2 2 / g, and the specific surface area of the reference example is 693.8 m 2 / g. In the powdered activated carbon molded bodies of Examples 1 and 2, the mesopore volume is increased compared to before the molding process, and the specific surface area is also increased, so that the adsorptivity is improved and the performance as an adsorbent is improved. The pore volume in Example 1 was 0.72 cc / g, which was larger than the 0.68 cc / g in the Reference Example. In Example 2, the pore volume was 0.67 cc / g, which is slightly smaller than the Reference Example but is about the same.
[0048] Therefore, the powdered activated carbon molded bodies of Examples 1 and 2 have improved performance as an adsorbent compared to the original powdered activated carbon, and the molding conditions of Examples 1 and 2 are conditions for improving the performance as an adsorbent compared to the original powdered activated carbon. Moreover, from Examples 1 to 4 and Comparative Examples 3 and 4, which have different heating temperatures, it is found that the higher the heating temperature, the smaller the specific surface area and pore volume. Therefore, it is found that the performance as an adsorbent is improved by setting the heating temperature for the SPS method to at least a temperature between Examples 1 and 2.
[0049] 4 shows electron microscope images (SEM images) of the surfaces of the powdered activated carbon molded bodies of Example 4 and Comparative Example 1, and mapping diagrams of carbon (C), oxygen (O) and silicon (Si) by energy dispersive X-ray analysis (EDS) of the same regions as the SEM images. For the powdered activated carbon molded body of Example 4, multiple needle-like structures with a diameter of 1 μm or less were observed in the SEM image, oxygen was not detected in the mapping diagram, and silicon was detected as being concentrated in the needle-like structures. On the other hand, for the powdered activated carbon molded body of Comparative Example 1, granular objects with a diameter of several μm were observed in the SEM image, and silicon and oxygen were detected as being concentrated in the granular objects in the mapping diagram, and it is presumed that oxidized silicon such as silicon dioxide is present.
[0050] Fig. 5 shows the results of X-ray diffraction analysis and the diffraction peak positions of β-SiC for the powdered activated carbon of the Reference Example and the powdered activated carbon molded bodies of Examples 1 to 4 and Comparative Examples 1 to 4. Diffraction peaks corresponding to β-SiC appear in the powdered activated carbon molded bodies of Examples 3 and 4. Therefore, it is considered that the needle-like structures shown in the SEM image of Example 4 in Fig. 4 are β-SiC. The heating temperatures in Examples 3 and 4 are 1400°C and 1600°C, respectively, which are lower than the melting point of silicon dioxide (1710°C). However, it is considered that the discharge plasma energy generated between the particles or in the pores of the powdered activated carbon by the SPS method promoted the following reaction to produce silicon carbide. SiO 2 + C → SiO + CO SiO + 2C → SiC + CO
[0051] In the powdered activated carbon molded bodies of Examples 3 and 4, the specific surface area and pore volume are smaller than those of the untreated powdered activated carbon of the reference example. On the other hand, as shown in FIG. 3, the height of the mesopore curve having a peak near 3.8 nm is higher in the powdered activated carbon molded bodies of Examples 3 and 4 than that of the untreated powdered activated carbon of the reference example, and the volume of the mesopores is increased. Therefore, the powdered activated carbon molded bodies of Examples 3 and 4 at least maintain the adsorption function as an adsorbent. And, since the powdered activated carbon molded bodies of Examples 3 and 4 contain silicon carbide that is chemically stable and does not react with, for example, nitric acid that dissolves carbon, the acid resistance is improved, and the molding conditions of Examples 3 and 4 are conditions for improving the performance as an adsorbent more than the original powdered activated carbon. Also, from Examples 1 to 4 and Comparative Examples 3 and 4, which have different heating temperatures, the diffraction peak of β-SiC appears when the heating temperature is high. Therefore, it can be seen that the performance as an adsorbent is improved if the heating temperature of the SPS method is set at a temperature at least between Examples 3 and 4.
[0052] In addition, a person skilled in the art can implement the present invention in a form in which various modifications are added to the above-described embodiment without departing from the spirit of the present invention, and the present invention includes such modifications. [Explanation of symbols]
[0053] 1: Pulse current sintering machine 2: Powdered activated carbon 3: Dice 4,5: Punch 6~8: 1st to 3rd spacers 9: Carbon felt 10: Casing 11: Pressurizing unit 12: Pulse power supply 13: Cooling mechanism 14: Vacuum unit 15: Radiation thermometer
Claims
1. A powdered activated carbon molded body is obtained by heating a plant-derived powdered activated carbon to 650°C to 800°C in a non-oxidizing atmosphere by an electric heating method and simultaneously applying mechanical pressure to mold the powdered activated carbon, the powdered activated carbon molded body containing silicon dioxide and having a larger specific surface area than the powdered activated carbon.
2. The powdered activated carbon molded body is obtained by heating plant-derived powdered activated carbon to 1400°C to 1600°C in a non-oxidizing atmosphere by an electric heating method and simultaneously applying mechanical pressure to mold the powdered activated carbon molded body, and is characterized by containing silicon carbide.
3. Bulk density is 0.5 g / cm 3 3. The powdered activated carbon molded body according to claim 1, wherein the powdered activated carbon molded body is a powdered activated carbon molded body.
4. A method for producing a powdered activated carbon molded product, comprising heating a plant-derived powdered activated carbon to 650°C to 800°C by an electric heating method in a non-oxidizing atmosphere and mechanically pressing the powdered activated carbon at 30 MPa.
5. A method for producing a powdered activated carbon molded body, comprising heating a plant-derived powdered activated carbon to 1400°C to 1600°C by an electric heating method in a non-oxidizing atmosphere and mechanically pressing the powdered activated carbon at 30 MPa.
Citation Information
Patent Citations
Method for preparing molded charcoal from powdered carbon
CN107629828A
Production of molded active carbon
JP1993132377A
Active carbon molded body and manufacturing method thereof, and adsorbent and storage material therewith
JP2017007879A
Sintered compact comprising activated carbon and its manufacturing method
JP2020050531A
Method for producing porous carbon material
JP7301300B1